Effect of inclined pile on seismic response of bridge abutments undergoing liquefaction—Induced lateral displacement: Case study of Nishikawa bridge in the 2011 Great East Japan earthquake - Xue, Ying-Ying; Wang, Xing-Gang; Cai, Fei (Frontiers in Materials, 2023)
It is reported that the inclined pile could be either beneficial or detrimental for the abutment they support in the condition of liquefaction – induced lateral displacement. To clarify the effect of inclined pile on seismic response of bridge abutments undergoing liquefaction – induced lateral displacement, numerical analyses were carried out on the damaged abutment that was supported by inclined piles and that was displaced riverwards 100 mm ~ 150 mm due to soil liquefaction during 2011 Great East Japan earthquake. Accordingly, a fully coupled dynamic effective stress finite element model was developed for the soil – pile – superstructure system. It was found that the shear failure of the bridge abutment was initialized from the inclined piles and then followed by the middle vertical pile. Moreover, the earthquake – induced liquefaction caused substantial lateral displacement of soils around the piles and thus dominated the backward rotation of the abutments supported by inclined piles. Additionally, the exclusion of the deck pinning effect may lead to a marked increase in the lateral displacement and rotation of abutments. If the abutment were supported by vertical piles, a much larger lateral displacement was expected and the promotion of the earth pressure behind the abutment was the main cause of the forward rotation of the piled abutment.